Modüler Konut Tasarımı için Geliştirilmiş Parametrik Tabanlı Bir Model Önerisi - Yardımcı, Burak (Fen Bilimleri Enstitüsü, 2013)
Özellikle 2. Dünya Savaşı sonrası doğan konut ihtiyacı ile ortaya çıkan toplu konut kavramı beraberinde standartlaşmayı getirmiştir. Kullanıcısının gereksinimlerini dikkate almadan, herkes için aynı tip ve yaklaşımla yaratılan yaşam alanları, daha sonraları hem mimari hem de kentsel anlamda sorgulanmaya başlanmış ve tasarımcıları alternatif tasarım yaklaşımlarına yönlendirmiştir. Tez çalışmasında 1960’lı yıllardan günümüze kadar olan süreçteki toplu konut tasarımında kullanılan alternatif yöntemler örnekler üzerinden incelenmiş ve alternatif bir tasarım modelinin nasıl bir yapıda olması üzerinde durularak yeni bir model yaratılmıştır. İkinci bölümde, ilk olarak alternatif toplu konut tasarımı yöntemleri üzerinde durulmuş ve farklılıkları ile benzerliklerine değinilmiştir. Üzerinde durulan bu farklı yöntemlere örnekler üzerinden yaklaşılmıştır. Örnekler üzerinden değerlendirmeler yapılmış ve yaklaşımlar ortaya konulmuştur. Her örnek bazında, tasarlanacak model çerçevesinde dikkate alınacak noktalar belirlenmiş ve gerektiği yerlerde eleştiriler ve eksik taraflar da belirtilmiştir. Alternatif toplu konut tasarımları geleneksel, ütopik ve bilgisayar destekli olmak üzere üç bölümde toplanmıştır. Her bölüm için farklı tarzda örnek projeler araştırılmıştır. Her projeden gerekli alanlar model için referans olarak alınmış ve model yapısında işlenerek değerlendirilmiştir. Üçüncü bölümde daha önce kritiği edilen örnekler de ele alınarak tasarlanan model anlatılmıştır. Tasarım modelini oluşturan parametreler, koşullar ve modelin diğer tüm özellikleri üzerinde durulmuştur. Model aracılığıyla elde edilen toplu konut projesinin tüm aşamaları anlatılmıştır. Modelin yaratılması süresince ortaya çıkan problemler, bu problemlerin nasıl aşıldığı, arayüzün işleyiş şeması ve son ürüne dair datalar detayları ile anlatılmıştır. Modelin yaratılmasında kullanılan program ve bu programdan elde edilen ürünün görselleştirilmesi üzerinde durulmuştur. Kullanıcının belirlediği parametrelerle gelişen ve gerçek zamanlı değişimleri gözlenen model ayrıntılı olarak, betik yapısı ile birlikte işlenmiştir. Modelin belirlenen kullanıcı senaryoları üzerinden oluşan plan şemaları oluşturulmuştur. Son bölümde ise tasarlanan modelin hangi yönlerden eksik kaldığı üzerinde durulmuştur. Başlangıçta belirlenen hangi hedeflere ulaşıldığı, hangilerine ulaşılamadığı belirlenmiştir. Gelecekte modelin geliştirleceği alanlar belirlenmiş ve ne yönde evrimleşmesi gerektiği üzerinde durulmuştur. Bu tür modellerin alternatif konut tasarımındaki rolünün önemine değinilerek tez tamamlanmıştır.

A wide-range housing problem was arisen especially after First World War all around the world. To solve that problem, new housing reproduction era started in an all cities that had lost the housing substance after the war. The standardization method had used to solve the need of that housing substance. The standardization approach that had developed with the Ford in motor industry called as T-model production had applied to the architecture field to solve the housing demand in a short time. Although this approach of standardization was successful to solve the problem of huge housing demand, it has caused negative effects on habitants. The new problematic community who has different needs and expectations even so living in same type of flats had appeared. The housing problem was caused by standardization forced the designers to search for a new method of housing design especially after 1960’s. The new alternative methods that were used in housing design are read in that research by examples. The examples are criticized with their advantages and disadvantages while creating a new model of modular housing design. In the second chapter of the thesis, the different methods that are used in housing design after 1960’s are exampled. The methods are researched by their examples that are divided in three parts as conventional methods, methods in utopian projects, and computer aided housing designs. All examples are criticized with their effects, advantages or disadvantages. The possible parts of the projects that will use in the model are explained with their reasons and the general explanation is made by all examples. The Scheepstimmermanstraat projects that were first planned by Jon Habraken then, designed by West 8 group, Malaqueira houses by Alvora Siza, Charles Correa’s Hudco project and Habitat 67 housing project by Moshe Safdie are researched as examples for conventional methods in housing design. Common positive characteristic of conventional examples are modular way of approach. In all projects, modular derivation method is used to reach geometries that are more complex with simple structures. Another positive characteristic that existed only in Malaqueira project is the design process that related to user need and time flow. The common negative characteristics of conventional examples are the limited creativity in projects that have only variability in planning scheme and facade design. Another method that is used for housing design can be seen in utopian projects during 70’s. Especially, the projects from Kisho Kurokawa, Arata Isozaki and Kenzo Tange are detailed criticized in that chapter. The main common point in all utopian projects is to see the building as an organical life form that grows by prescribed scheme. The designers tried to create living habitats in all projects. They planned a core that contains all service systems, infrastructures and vertical circulation system inside and placed the living units at the edges of that core. The complexity of all service systems and structure is solved by that core system easily. However, the negative characteristic of utopian projects is the limited creativity in living units. All the living units are just repitition of themselves and there is not any variability in living modules. The last method is used for housing design, that is searched in thesis is computer aided design method. Computer aided design method was firstly started as non-parametrical projects during 90’s. The vertical Project that was designed by MVRDV group is read as first example in thesis. T-trees Social Housing project is second example to understand the modularity in evolution. Other examples, which are discussed for computer aided design method, are Barcode project and MHAS Modular Housing Arrangement System. Nearly all examples are based on the modularity approach as the conventional housing projects. However, with the development of CAD systems the number of the parametric projects is increased. The aim of reaching variability by the evolution of modules is common specialty in projects that are developed with computer aided design method. Designers tried to reach geometries that are more complex by starting from one module and they defined several living units. Generally, in all examples, the relation between living areas and core system has important role. Designers tried to place the core system first by defined rules and then try to reach geometries environs of a core. Another characteristic of computer-aided systems is their interface. Some models are based on real-time change interface although some of them are not. The real-time change interface specialties criticized pozitivly and try to adapt in new model that will create. The algorithms of all examples are examined carefully and try to find the similar way of algorithm using in new model. In the third chapter, the new model is defined with its details in all phases. The reason of choosing the program is explained and the program that used to create the model was being introduced with its characteristics, interface and work scheme. The characteristic of the program is classified and the reasons during the selection of the program are told. Other programs and work schemas was presented with the reasons for choosing them. All the parameters, circumstances and all other specialties of the model are explained with their causes and results. The workflow of the model is shown with images and all problems that are existed during the process are defined. All the parts of the model such as sliders, parameters, export and library specifications and interface are explained and the real time changes are shown with images. The role of the parameters is explained with their ranges and numeric specialties. The algorithms of the model are written in that part with explaining the codes and parameters for relevant researchers. The optimal values and their reasons are explained in that part for parameters. The parts of the script are explained with visualizations that are prepared by other programs. The export and import relations of the program with other CAD programs are introduced. The project that was created by the model was converted to the other data files to complete presentation. After that, the project was visualized and the project was completed. In the last part of thesis, the new model is criticized with its negative and positive characteristics. The deficient points of the model were explained with their reasons and the goals for future researches are defined. The possible evaluation of the model in near future is explained clearly and the boundary of the parametric model is drawn. The possible areas of expertise and usage of the model is being told. The studies that can be develop after the thesis project and its prospective future is discussed. Future targets of the model was explained with their target aims was explained. The missing parts of the model such as database creation, data mining process, variability in core parameters and the visualization process is written with their roles in near future works. The way of attachment of these properties to the future model is explained clearly. The thesis project concluded with the explanation of the importance role of the similar models in housing design process and their potential effects during the housing design process. The importance of the variability of the last product that is created by model algorithm is discussed with architectural prospective.
A Parametric Model Proposal For Modular Housing Design
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: Mimarlık; mimari tasarımda bilişim; parametrik tasarım; kullanıcı özellikleri; toplu konut tasarımı; architecture; computer aided design; paremetric design; user-based design; social housing; housing; user parameters